Relative susceptibilities of Brazilian vegetation to airborne fluoride - Weinstein, Leonard H.; Hansen, Karen S. (Pesquisa Agropecuaria Brasileira, 2014)
Airborne fluorides are the most toxic of the common air pollutants to plants. Compounds such as hydrogen fluoride, silicon tetrafluoride, and fluosilicic acid are byproducts of the manufacture of aluminum, phosphate fertilizer, steel, glass, fluoroplastics, and of coal combustion, but there are also many other lesser sources. Fluoride is not only highly toxic but it also accumulates in the plant, especially in the foliage. Ingestion by herbivores can induce a dental and skeletal disease called "fluorosis" in many species. The fluoride accumulated in plants poses little danger to man because the amount of fluoride that might be ingested in the average diet would be relatively low compared with herbivores. Because most of the fluoride in plants accumulates in foliage, ingestion of stems, seeds and fruits, and roots should not increase fluoride significantly. During the course of inspecting vegetation at four aluminum smelters in Brazil in 1982, 1983 and 1986, more than 230 species of plants from tropical, semi-tropical, and temperate areas were ranked according to their relative susceptibility to fluoride, based upon the degree of foliar injury produced. This may not be a measure of yield response, however. Species are classified according to standard botanical nomenclature, along with the vernacular names used in Brazil and the U.S.